The Mayae Tradition and the Dynamics of Citizenship Politics: Local Wisdom Study of the Maregam Community in Tidore Islands City - Wahyudin Noe; Abd. Firman Bunta; Triyanto; Misnah; Aziah Ismail; Yuli Adhani; M. Azrul Marsaoly (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
This research is motivated by the researchers’ concern about the low level of public awareness to actively participate in political life, such as being apathetic towards political choices and the strengthening of a patronage political culture in the form of political support in every general election. However, this is not reflected in the Maregam community in Tidore Islands City, where political attitudes and choices appear more active and varied because they are influenced by the “MAYAE” tradition (mutual help). The purpose of this research is to further and in-depth analyze the dynamics of citizenship politics in the Maregam community based on the “Mayae” tradition. This research used a qualitative approach with a case study. The results show that the dynamics of citizenship politics in the Maregam community based on the “Mayae” tradition are evident in: 1) active involvement in every aspect of political life, 2) respect for different political choices, 3) consensual decision-making as a way to reach agreement and solve problems, and 4) the candidate's track record and concern for citizens as the primary consideration in choice-making. The findings of this study constitute a good model of citizenship political participation that to be recommended to other communities, and serve as a basis for further research development.